(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2024)
This article presents and discusses Za‘ba’s book, Rahsia Ejaan Jawi (REJ), in which he describes in great detail the system and characteristics of the Jawi script, both of which form the basis in the formulation of his method of spelling Malay words when using this particular medium of writing. The history of Jawi is discussed based on categories of symbols or letters given in their original forms in the Arabic script, and with this the variations in the shape of each symbol or letter in words; such variations are known as allographs. The unity of symbol and sound is important in this method, which also preserves the aesthetics of the Jawi script. There are many “reminders” given in the guidelines for Jawi script spelling, among them is to not apply the Rumi spelling method (alphabet system) because there is no similarity with the former (syllabic system). Due to the importance of standardization of Jawi spelling for the Malay language, Za‘ba’s other reminder is not to change the spelling of words that have been long accepted, including loanwords from Arabic. Should a change be necessary, the opinions of the community should be taken into consideration. Full text: PDF